A Comparative Analysis Of Abortion For Rape Victims From The Perspectives Of Fiqh Jinayah And Indonesian Positive Law - Sumantri Adenin; Helmi Basri; M Ihsan; Deri Eka Putra; Muh Rizki (Hukum Islam, 2026)
This article comparatively analyzes abortion practices and regulations for rape victims from the perspectives of Islamic jurisprudence (fiqh jinayah) and Indonesian positive law. The study aims to examine the normative foundations, limitations, and legal consequences related to the protection of rape victims in both legal systems. This research employs normative legal methods, drawing on classical and contemporary Islamic legal sources as well as national legislation governing abortion. The findings indicate that Islamic jurisprudence (fiqh jinayah) fundamentally prohibits abortion; however, in certain emergency circumstances—such as pregnancies resulting from rape—it allows abortion based on the principle of hifz al-nafs (protection of life). Meanwhile, Indonesian positive law permits abortion for rape victims in a limited manner, subject to strict legal requirements, particularly concerning gestational age and medical procedures. This study underscores the importance of a legal approach that prioritizes substantive justice and the protection of victims’ rights. Furthermore, a humane response to abortion resulting from rape requires the reconciliation of the values of Islamic law and national law. Keywords: Abortion, Rape, Islamic Jurisprudence, Indonesian Positive Law